INTERACTIVE DIGITAL BOARD IN EARLY CHILDHOOD: ENHANCING NUMERACY, GRAPHOMOTOR SKILLS, COLLABORATION, AND CHARACTER - Khusnatul Mawaddah; Harisma Fatihatul Hayyu; Elfa Yuliana Nasution; Ria Arista Asih; Erna Yayuk; Beti Istanti Suwandayani; Arina Restian (Universitas Islam Negeri Mataram, 2026)
This study examines how the pedagogical implementation of an Interactive Digital Board (IDB) enhances the integrated development of numeracy, graphomotor skills, collaboration, and character in early childhood education. Graphomotor skills in this study refer to fine motor abilities related to early writing activities, including tracing, drawing, and symbol formation. Employing a qualitative descriptive case study design, the research was conducted in a natural classroom setting at PAUD At-Taqwa, Bojonegoro, involving 15 children aged 4–6 years and two teachers. Data were collected through non-participant observation and documentation of IDB-integrated thematic learning activities. The findings reveal four key outcomes: (1) IDB-mediated activities effectively bridge concrete and abstract numerical understanding; (2) stylus-based interaction supports the development of graphomotor control through repetitive and error-tolerant practice; (3) multi-touch features facilitate peer interaction, negotiation, and collaborative problem-solving; and (4) the implementation of the “queue technique” (Teknik Antre) promotes patience, discipline, and honesty. This study contributes to the literature by providing empirical evidence of a holistic pedagogical approach that integrates multiple developmental domains through a single digital learning medium. In practice, the findings highlight the importance of context-sensitive and teacher-designed strategies for optimising the use of digital technology, particularly in resource-limited early childhood classrooms